Hot compress patch for pilots and preparation method of hot compress patch

By using non-woven bags to pack mixed heating materials and temperature-controlling particles in the hot compress for pilots, the problems of short heating time and inappropriate temperature of existing hot compresses are solved, and the effect of stable heating is achieved for a long time is achieved, effectively alleviating the fatigue of pilots and improving flight safety.

CN119908894APending Publication Date: 2025-05-02FOURTH MILITARY MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411860878.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The current pilots' heat compresses have a short time and an inappropriate heat temperature, which leads to poor heat compresses and may cause damage to the skin and blood vessels, affecting flight safety.

Method used

A heat generating layer is prepared by mixing heat generating materials in a non-woven bag, combining hot melt pressure-sensitive adhesive and release film to form an adhesive layer and an anti-adhesive isolation layer, and temperature-controlled particles are used to stabilize the heating temperature and extend the heating time.

Benefits of technology

The heating time is extended and the heating temperature is stabilized, ensuring that the pilot can relieve fatigue in a timely and effective manner during flight and improve flight safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193172000000101
    Figure BDA0005193172000000101
  • Figure BDA0005193172000000111
    Figure BDA0005193172000000111
Patent Text Reader

Abstract

The invention discloses a hot compress patch for a pilot and a preparation method of the hot compress patch, and belongs to the technical field of hot compress patches for flight, the hot compress patch comprises a heating layer, a bonding layer and an anti-bonding isolation layer, and specifically, the heating layer is prepared from iron powder, vermiculite, activated carbon, sodium chloride, water and temperature control particles; the temperature control particles are prepared to absorb, store and release heat released by reaction of the iron powder and the like, so that the heating time of the hot compress patch is prolonged, the heating temperature is controlled, and the problems that a hot compress patch prepared by a conventional method is short in heating time and inappropriate in heating temperature are solved. A zipper type opening and closing bag structure can be prepared in the flying suit, so that the prepared hot compress paste is pasted in the bag, or the hot compress paste is directly pasted on a part needing hot compress, long-time hot compress at proper temperature is realized, fatigue in the long-time flying process is relieved in time, and flying safety is better guaranteed; the prepared hot compress patch is light in weight and convenient to replace, and has a good application prospect in the aspect of relieving fatigue caused by long-time flight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hot compress patches for flying, and in particular to a hot compress patch for pilots and a preparation method thereof. Background Art

[0002] Problems such as physical fatigue and mental fatigue generated by flight crews in the course of performing their missions are becoming increasingly prominent. Complex operating systems and dynamic demands require drivers to have a high level of cognitive ability. If the fatigue state of flight crews is not improved promptly and effectively, they will often experience fatigue phenomena such as inattention, reduced work efficiency, and decreased judgment and operational ability, posing a threat to flight safety. Therefore, alleviating flight fatigue is of great significance to flight safety.

[0003] At present, the intervention methods for flight fatigue mostly use exercise, diet, sleep and drugs, etc. These methods are mostly carried out before or after the flight, and cannot timely relieve the fatigue generated during the flight. Hot compress is a physical therapy method that has the effects of dilating blood vessels, improving local blood circulation, promoting local metabolism, and relieving fatigue. It can effectively relax muscles, reduce fatigue, and achieve the effect of relieving pain and relaxing emotions. Hot compress patches are commonly used hot compress products that can achieve good hot compress effects, and hot compress patches can be placed directly in flight suits, so that hot compress treatment can be carried out in time during the flight process to achieve the effect of timely relieving flight fatigue. However, the hot compress patches prepared by traditional conventional methods are generally prepared by mixing iron powder, water, activated carbon and inorganic salts. During use, it is easy to have problems such as short heating time and high or too low temperature. Not only can the ideal hot compress effect not be achieved, but the overheating temperature will damage the subcutaneous tissue and blood vessels at the hot compress site, causing safety problems.

[0004] Therefore, there is a need to find a method for preparing a hot compress patch suitable for pilots to solve the problem that the hot compress patch prepared by the conventional method has a short heating time and an inappropriate heating temperature, and thus cannot achieve a good hot compress effect. A hot compress patch with a long heating time and a suitable and stable heating temperature should be prepared to provide timely hot compress treatment to flight personnel during the flight, relieve fatigue, and thus better ensure flight safety. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a hot compress patch for pilots and a preparation method thereof, so as to solve the problem that the hot compress patch prepared by the conventional method has a short heating time and an inappropriate heating temperature, thereby failing to achieve a good hot compress effect.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A hot compress patch for pilots comprises a heating layer, an adhesive layer and an anti-sticking isolation layer. The heating layer is obtained by filling a non-woven bag with a mixed heating material.

[0008] Furthermore, the adhesive layer is a hot-melt pressure-sensitive adhesive; and the anti-sticking isolation layer is a release film.

[0009] Furthermore, the mixed heating material comprises the following raw materials:

[0010] Iron powder, vermiculite, activated carbon, sodium chloride, water, graphite, lauric acid, L-glutamine, curdlan, 3-aminopropanol.

[0011] Furthermore, the particle size of the iron powder is 0.3-0.9 mm; the particle size of the vermiculite is 0.1-0.2 mm; and the particle size of the activated carbon is 0.5-1 mm.

[0012] The present invention also discloses a preparation method of the pilot heat compress patch, and the preparation method is specifically as follows:

[0013] The mixed heating material is put into a non-woven bag and pressed into a sheet to obtain a heating layer; a hot-melt pressure-sensitive adhesive is evenly coated on one side of the heating layer to form an adhesive layer, and then a release film is adhered to form an anti-sticking isolation layer. After drying for 2-5 minutes, a vacuum packaging machine is used to vacuum package the layer to obtain a finished hot compress patch.

[0014] Further, the preparation method of the mixed heating material is as follows:

[0015] (1) adding graphite to a 20% by volume ethanol solution and stirring and dispersing the solution, adjusting the pH of the dispersion to 9, then adding L-glutamine, heating the solution to 40-50° C. and stirring the solution for reaction for 4-8 hours, filtering and removing the filtrate after the reaction is completed, washing the solution with water and drying the solution at 60° C. to obtain modified graphite; heat treating the modified graphite at 800-1000° C. for 8-12 seconds to obtain modified expanded graphite;

[0016] (2) heating lauric acid to 60° C. and stirring to melt, then adding 3-aminopropanol, stirring to react for 2-3 hours, cooling to room temperature after the reaction is completed and standing overnight to obtain a lauric acid mixture; heating the lauric acid mixture to 85° C. and melting it, adding modified expanded graphite and mixing evenly, then dissolving curdlan in water and adding it, mixing evenly, cooling to room temperature, drying at 50° C. and grinding through a 40-mesh sieve to obtain temperature-controlled particles;

[0017] (3) The iron powder, vermiculite, activated carbon and temperature control particles are mixed evenly, and then sodium chloride is dissolved in water and added, and the mixture is stirred and mixed at a speed of 200 r / min for 5 minutes to obtain a mixed heating material.

[0018] The hot compress patch for pilots should effectively relieve the pilot's fatigue during flight, and needs to meet the requirements of long heating time and appropriate heating temperature. The hot compress patch with long heating time can avoid the pilot's frequent switching operations during flight, and the appropriate heating temperature can avoid overheating during flight to burn the skin and cause hidden dangers to flight safety, while ensuring a good hot compress effect. Therefore, the present invention improves the conventional hot compress patch to prepare a hot compress patch with long heating time and appropriate heating temperature, so as to effectively relieve the pilot's flight fatigue and better ensure flight safety.

[0019] Specifically, the present invention uses iron powder, activated carbon and the like as raw materials to prepare heating materials, which are loaded into a non-woven bag to prepare a heating layer. When used, the iron powder can undergo an oxidation reaction with the air to release heat, thereby achieving hot compress. In order to ensure that the released heat can be fully utilized and the temperature is maintained within a suitable hot compress temperature range, the present invention also prepares a temperature-controlling particle mixture to prepare a heating layer, so as to achieve the effect of hot compress at a suitable temperature for a long time.

[0020] Specifically, the present invention adopts lauric acid, a phase change heat storage material with a phase change temperature of about 45°C, and mixes it with graphite with good thermal conductivity to prepare temperature control particles, which are added to a hot compress patch. When the iron powder and the like react to release heat, the lauric acid in the temperature control particles utilizes its own phase change energy storage performance to absorb excess heat in time and store it, and then releases it when the temperature drops, thereby reducing heat waste and extending the heating time of the hot compress patch. At the same time, the heating temperature is stabilized at about the phase change temperature. This temperature is suitable for hot compresses to relieve fatigue, and can better exert the effect of the hot compress patch.

[0021] Lauric acid heat storage material utilizes its solidification to release heat and its melting to absorb heat to absorb, store and release the heat released by reactions such as iron powder. After melting, lauric acid has fluidity and will flow and aggregate into clumps under the influence of gravity, affecting the uniform heating of the hot compress and causing the heating temperature to be unstable. Therefore, lauric acid needs to be processed to inhibit its flow in the hot compress and ensure uniform heating of the hot compress.

[0022] Specifically, the present invention first adopts L-glutamine to react with graphite to change the surface chemical properties and molecular chain structure of graphite, improve the interaction force between graphite and lauric acid molecules, and then conducts high-temperature heat treatment to expand it to obtain modified expanded graphite with more porous structure. When mixed with lauric acid to prepare temperature-control particles, lauric acid can be adsorbed into the porous structure of the modified expanded graphite, and under the enhanced intermolecular interaction force, lauric acid is difficult to fall off from the modified expanded graphite, thereby fixing it and inhibiting its flow. However, graphite has excellent thermal conductivity, and excessive addition will lead to excessive heat transfer and heat loss, shortening the heating time of the hot compress patch. Therefore, curdlan is added, which forms a gel three-dimensional network structure after heating to fix lauric acid in the network structure, and acts together with graphite to inhibit the melting and flow of lauric acid, thereby ensuring the heating uniformity of the hot compress patch. At the same time, it can also prevent lauric acid from flowing after melting to embed iron powder, thereby inhibiting the heating reaction, thereby ensuring the good effect of the hot compress patch.

[0023] In order to better extend the continuous heating time of the hot compress patch, the present invention also adds 3-aminopropanol to treat lauric acid, adjusts the lauric acid molecular chain structure to enhance the hydrogen bonding ability between lauric acid molecules, thereby improving the interaction force between lauric acid molecules, increasing the phase change latent heat of lauric acid, better absorbing, storing and releasing heat, reducing heat loss and thus extending the continuous heating time.

[0024] Furthermore, in the step (1), the mass ratio of graphite to L-glutamine is (5-10): (0.5-1).

[0025] Furthermore, in the step (2), the mass ratio of lauric acid to 3-aminopropanol, modified expanded graphite, and curdlan is (45-90):(6-12):(5-10):(1-2).

[0026] Furthermore, in step (3), the mass ratio of iron powder, vermiculite, activated carbon, temperature-control particles, sodium chloride and water is (900-950): (30-70): (40-60): (50-100): (20-40): (450-550).

[0027] Beneficial effects:

[0028] The present invention processes graphite and lauric acid to prepare temperature-control particles and adds the particles to a hot compress patch. The lauric acid in the temperature-control particles can utilize its phase change properties to effectively absorb the heat released by reactions such as iron powder, store it, and release it, thereby stabilizing the heating temperature of the hot compress patch while reducing heat waste and extending the heating time, thereby achieving timely hot compress treatment for flight personnel, effectively alleviating fatigue, and better ensuring flight safety. DETAILED DESCRIPTION

[0029] The present invention will be described in detail below with reference to specific embodiments:

[0030] The invention discloses a hot compress patch for pilots and a preparation method thereof. Before preparing the hot compress patch, a mixed heating material needs to be prepared. When preparing the mixed heating material, raw materials are used, wherein the iron powder particle size is 0.4 mm, the vermiculite particle size is 0.1 mm, and the activated carbon particle size is 0.6 mm. Then, the mixed heating material is further prepared, as shown below.

[0031] Example 1: Preparation of mixed heating material

[0032] (1) adding 7 g of graphite to 140 g of 20% ethanol solution by volume and stirring to disperse, adjusting the pH of the dispersion to 9, then adding 0.7 g of L-glutamine, heating to 45° C. and stirring to react for 6 h, filtering and removing the filtrate after the reaction is completed, washing with water twice and drying at 60° C. to obtain modified graphite; placing the modified graphite in a resistance furnace and heat treating at 900° C. for 10 s to obtain modified expanded graphite;

[0033] (2) 65 g of lauric acid was heated to 60° C. and stirred to melt, and then 7 g of 3-aminopropanol was added, stirred to react for 2-3 h, and after the reaction was completed, the mixture was cooled to room temperature and allowed to stand overnight to obtain a lauric acid mixture; the lauric acid mixture was heated to 85° C. and melted, and then 7 g of modified expanded graphite was added and mixed evenly, and then 1.5 g of curdlan was dissolved in 150 g of water and added, mixed evenly, cooled to room temperature, dried at 50° C., and then ground through a 40-mesh sieve to obtain temperature-controlled particles;

[0034] (3) 920 g of iron powder, 50 g of vermiculite, 50 g of activated carbon and 70 g of temperature control particles were mixed uniformly, and 30 g of sodium chloride was dissolved in 500 g of water and then added, and the mixture was stirred and mixed at a speed of 200 r / min for 5 min to obtain a mixed heating material.

[0035] Example 2: Preparation of mixed heating material

[0036] (1) adding 5 g of graphite to 100 g of ethanol solution with a volume fraction of 20% and stirring to disperse, adjusting the pH of the dispersion to 9, then adding 0.5 g of L-glutamine, heating to 40° C. and stirring to react for 8 h, filtering and removing the filtrate after the reaction is completed, washing with water twice and drying at 60° C. to obtain modified graphite; placing the modified graphite in a resistance furnace and heat treating at 800° C. for 12 s to obtain modified expanded graphite;

[0037] (2) 45 g of lauric acid was heated to 60° C. and stirred to melt, and then 6 g of 3-aminopropanol was added, stirred to react for 2 h, and after the reaction was completed, the mixture was cooled to room temperature and allowed to stand overnight to obtain a lauric acid mixture; the lauric acid mixture was heated to 85° C. and melted, and then 5 g of modified expanded graphite was added and mixed evenly, and then 1 g of curdlan was dissolved in 100 g of water and added, and the mixture was cooled to room temperature after being mixed evenly, and then dried at 50° C. and ground through a 40-mesh sieve to obtain temperature-controlled particles;

[0038] (3) 900 g of iron powder, 30 g of vermiculite, 40 g of activated carbon and 50 g of temperature control particles were mixed evenly, and 20 g of sodium chloride was dissolved in 450 g of water and then added, and the mixture was stirred and mixed at a speed of 200 r / min for 5 min to obtain a mixed heating material.

[0039] Example 3: Preparation of mixed heating material

[0040] (1) adding 10 g of graphite to 200 g of ethanol solution with a volume fraction of 20% and stirring to disperse, adjusting the pH of the dispersion to 9, then adding 1 g of L-glutamine, heating to 50° C. and stirring to react for 4 h, filtering and removing the filtrate after the reaction is completed, washing with water twice and drying at 60° C. to obtain modified graphite; placing the modified graphite in a resistance furnace and heat treating at 1000° C. for 8 s to obtain modified expanded graphite;

[0041] (2) 90 g of lauric acid was heated to 60° C. and stirred to melt, and then 12 g of 3-aminopropanol was added, stirred to react for 3 h, and after the reaction was completed, the mixture was cooled to room temperature and allowed to stand overnight to obtain a lauric acid mixture; the lauric acid mixture was heated to 85° C. and melted, and then 10 g of modified expanded graphite was added and mixed evenly, and then 2 g of curdlan was dissolved in 200 g of water and added, and the mixture was cooled to room temperature after being mixed evenly, and then dried at 50° C. and ground through a 40-mesh sieve to obtain temperature-controlled particles;

[0042] (3) 950 g of iron powder, 70 g of vermiculite, 60 g of activated carbon and 100 g of temperature control particles were mixed evenly, and 40 g of sodium chloride was dissolved in 550 g of water and then added, and the mixture was stirred and mixed at a speed of 200 r / min for 5 min to obtain a mixed heating material.

[0043] Comparative Example 1: Preparation of mixed heating material

[0044] In contrast to Example 1, the only difference is that in the preparation of the mixed exothermic material in Comparative Example 1, L-glutamine is not added in step (1) to modify the graphite, and the expanded graphite is directly subjected to high-temperature heat treatment and added in step (2), as shown below:

[0045] (1) 7 g of graphite was placed in a resistance furnace and heat treated at 900° C. for 10 s to obtain expanded graphite;

[0046] (2)-(3) are the same as in Example 1.

[0047] Comparative Example 2: Preparation of mixed heating material

[0048] In contrast to Example 1, the only difference is that in Comparative Example 2, when preparing the mixed heating material, the graphite is not subjected to high-temperature heat treatment, and the modified graphite is directly prepared and added in step (2), as shown below:

[0049] (1) adding 7 g of graphite to 140 g of 20% ethanol solution by volume, stirring and dispersing, adjusting the pH of the dispersion to 9, then adding 0.7 g of L-glutamine, heating to 45° C. and stirring to react for 6 h, filtering and removing the filtrate after the reaction is completed, washing with water twice, and drying at 60° C. to obtain modified graphite;

[0050] (2)-(3) are the same as in Example 1.

[0051] Comparative Example 3: Preparation of mixed heating material

[0052] In contrast to Example 1, the only difference is that the original step (1) is missing when preparing the mixed heating material in Comparative Example 3, and the graphite is not processed, but conventional graphite is used, as shown below:

[0053] (1) 65 g of lauric acid is heated to 60° C. and stirred to melt, then 7 g of 3-aminopropanol is added, stirred to react for 2-3 h, and after the reaction is completed, cooled to room temperature and allowed to stand overnight to obtain a lauric acid mixture; the lauric acid mixture is heated to 85° C. and melted, and then 7 g of graphite is added and mixed evenly, and then 1.5 g of curdlan is dissolved in 150 g of water and added, mixed evenly, cooled to room temperature, dried at 50° C., and then ground through a 40-mesh sieve to obtain temperature-controlled particles;

[0054] (2) 920 g of iron powder, 50 g of vermiculite, 50 g of activated carbon and 70 g of temperature control particles were mixed evenly, and 30 g of sodium chloride was dissolved in 500 g of water and then added, and the mixture was stirred and mixed at a speed of 200 r / min for 5 min to obtain a mixed heating material.

[0055] Comparative Example 4: Preparation of mixed heating material

[0056] In contrast to Example 1, the only difference is that 3-aminopropanol is not added in step (2) when preparing the mixed exothermic material in Comparative Example 4, as shown below:

[0057] (1) Same as Example 1;

[0058] (2) 65 g of lauric acid was heated to 85° C. to melt, and then 7 g of modified expanded graphite was added and mixed evenly, and then 1.5 g of curdlan was dissolved in 150 g of water and added, and the mixture was cooled to room temperature after being mixed evenly, dried at 50° C., and then ground through a 40-mesh sieve to obtain temperature-controlled particles;

[0059] (3) Same as Example 1.

[0060] Comparative Example 5: Preparation of mixed heating material

[0061] In contrast to Example 1, the only difference is that in Comparative Example 5, curdlan is not added when preparing the mixed exothermic material, as shown below:

[0062] (1) Same as Example 1;

[0063] (2) heating 65 g of lauric acid to 60° C. and stirring to melt, then adding 7 g of 3-aminopropanol, stirring to react for 2-3 h, cooling to room temperature after the reaction is completed and standing overnight to obtain a lauric acid mixture; heating the lauric acid mixture to 85° C. and melting, adding 7 g of modified expanded graphite and mixing evenly, cooling to room temperature, drying at 50° C. and grinding through a 40-mesh sieve to obtain temperature-controlled particles;

[0064] (3) Same as Example 1.

[0065] Comparative Example 6: Preparation of mixed heating material

[0066] In contrast to Example 1, the only difference is that the mixed exothermic material in Comparative Example 6 is prepared by a room temperature method without adding temperature control particles, as shown below:

[0067] 920g of iron powder, 50g of vermiculite and 50g of activated carbon were mixed evenly, 30g of sodium chloride was dissolved in 500g of water and then added, and the mixture was stirred at 200r / min for 5min to obtain a mixed heating material.

[0068] Example 4: Preparation of hot compress patch

[0069] The mixed heating material prepared according to the method of Example 1 is loaded into a non-woven bag with a size of 96×140 mm in an amount of about 50 g per bag, and pressed into a sheet to obtain a heating layer; a hot-melt pressure-sensitive adhesive is evenly coated on one side of the heating layer to form an adhesive layer, and then a release film is adhered to form an anti-sticking isolation layer. After drying for 2-5 minutes, a vacuum packaging machine is used to vacuum package to obtain a hot compress patch.

[0070] Experiment 1: Lauric acid fixation ability test

[0071] The temperature-controlling particle experimental samples were prepared according to the methods of Example 1 and Comparative Examples 1-5, and the fluidity of the lauric acid after thermal melting in each group of temperature-controlling particles was tested. The specific experimental method is as follows:

[0072] The temperature-controlled particles were wrapped with gauze and placed in a 60°C oven for heat treatment for 30 minutes, then taken out and cooled at room temperature for 30 minutes, and then heat treated and cooled for 10 times in the same manner, and the mass of the particles before and after the treatment was recorded. The fluidity of lauric acid in the temperature-controlled particles was detected by the mass loss rate of the temperature-controlled particles (lauric acid loss rate), mass loss rate = (mass before treatment - mass after treatment) / mass before treatment × 100%, and the data were shown in Table 1:

[0073] Table 1

[0074]

[0075] According to the data analysis in Table 1:

[0076] (1) The graphite and curdlan in the temperature-control particles prepared by the method of Example 1 of the present invention have a good ability to fix lauric acid. After several thermal melts, the lauric acid does not escape and flow. It can be seen that the method of the present invention is used to prepare lauric acid into temperature-control particles, which can enable lauric acid to effectively exert its phase change heat storage performance while inhibiting its flow, thereby ensuring the heat uniformity of the hot compress and the reactivity of the internal raw materials such as iron powder.

[0077] (2) In comparative example 1, L-glutamine was not used to modify the graphite during the preparation of the temperature-controlled particles, and thus the interaction force between the graphite and the lauric acid molecules was relatively small, which reduced the retention capacity of lauric acid and caused part of the lauric acid to be lost after melting. In Example 1, L-glutamine was used to modify the graphite, which increased the hydrogen bonding force and electrostatic force between the graphite and the lauric acid molecules, increased the retention capacity of lauric acid, and inhibited the loss of lauric acid. In comparative example 2, graphite was not expanded during the preparation of the temperature-controlled particles, and the pore structure of graphite was relatively reduced, thereby reducing the capacity to accommodate lauric acid. In comparative example 5, curdlan was not added during the preparation of the temperature-controlled particles, and the melting loss rate of lauric acid increased significantly compared with that in Example 1. This is because the gel network structure formed after the curdlan was added in Example 1 works together with graphite to fix lauric acid in the pores, thereby inhibiting the flow of lauric acid.

[0078] Experiment 2: Hot compress patch performance test

[0079] The mixed heating materials prepared in Example 1 and Comparative Examples 1-6 were prepared into finished hot compress patches according to the method of Example 4, and then the maximum heating temperature, the minimum heating temperature and the heating duration at room temperature of 25°C were measured, and the data obtained are shown in Table 2.

[0080] Table 2

[0081]

[0082] According to the data analysis in Table 2:

[0083] (1) The heating temperature of the hot compress patch prepared according to the method of the present invention is stable, and the maximum heating temperature and the minimum heating temperature are both stable at about 44°C with little fluctuation, and the continuous heating time is long, which can reach 16.8 hours. This shows that the hot compress patch prepared according to the method of the present invention can continuously generate heat for a long time at an appropriate temperature, thereby exerting a good hot compress effect and effectively relieving fatigue.

[0084] (2) In Comparative Examples 1, 2, 3 and 5, the melting and flow of lauric acid affects the distribution of the internal heating material, thereby affecting the stability of the heating temperature and the reaction activity of the heating material. In Comparative Example 6, a conventional method is used to prepare a hot compress patch. In the absence of temperature-controlling particles, the heating of the hot compress patch is unstable and the heating time is greatly shortened.

[0085] (3) In comparative example 4, 3-aminopropanol was not added during the preparation of the hot compress patch, the interaction force between lauric acid molecules was reduced, the phase change heat storage performance was poor, the heat loss increased, and thus the action time of the hot compress patch was reduced.

[0086] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A hot compress for pilots, characterized in that: The hot compress patch comprises a heating layer, an adhesive layer and an anti-sticking isolation layer. The heating layer is obtained by filling a non-woven bag with mixed heating materials.

2. A hot compress for pilots according to claim 1, characterized in that: The adhesive layer is a hot-melt pressure-sensitive adhesive; the anti-sticking isolation layer is a release film.

3. A hot compress for pilots according to claim 2, characterized in that: The mixed heating material comprises the following raw materials: Iron powder, vermiculite, activated carbon, sodium chloride, water, graphite, lauric acid, L-glutamine, curdlan, 3-aminopropanol.

4. A hot compress for pilots according to claim 3, characterized in that: The particle size of the iron powder is 0.3-0.9 mm; the particle size of the vermiculite is 0.1-0.2 mm; and the particle size of the activated carbon is 0.5-1 mm.

5. A method for preparing a hot compress for pilots, characterized in that: The preparation method is as follows: The mixed heating material is put into a non-woven bag and pressed into a sheet to obtain a heating layer; a hot-melt pressure-sensitive adhesive is evenly coated on one side of the heating layer to form an adhesive layer, and then a release film is adhered to form an anti-sticking isolation layer. After drying for 2-5 minutes, a vacuum packaging machine is used to vacuum package the layer to obtain a finished hot compress patch.

6. The method for preparing a hot compress patch for pilots according to claim 5, characterized in that: The preparation method of the mixed heating material is as follows: (1) adding graphite to a 20% by volume ethanol solution and stirring and dispersing the solution, adjusting the pH of the dispersion to 9, then adding L-glutamine, heating the solution to 40-50° C. and stirring the solution for reaction for 4-8 hours, filtering and removing the filtrate after the reaction is completed, washing the solution with water and drying the solution at 60° C. to obtain modified graphite; placing the modified graphite in a resistance furnace and heat treating the solution at 800-1000° C. for 8-12 seconds to obtain modified expanded graphite; (2) heating lauric acid to 60° C. and stirring to melt, then adding 3-aminopropanol, stirring to react for 2-3 hours, cooling to room temperature after the reaction is completed and standing overnight to obtain a lauric acid mixture; heating the lauric acid mixture to 85° C. and melting it, adding modified expanded graphite and mixing evenly, then dissolving curdlan in water and adding it, mixing evenly, cooling to room temperature, drying at 50° C. and grinding through a 40-mesh sieve to obtain temperature-controlled particles; (3) The iron powder, vermiculite, activated carbon and temperature control particles are mixed evenly, and then sodium chloride is dissolved in water and added, and the mixture is stirred and mixed at a speed of 200 r / min for 5 minutes to obtain a mixed heating material.

7. The method for preparing a hot compress for pilots according to claim 6, characterized in that: In the step (1), the mass ratio of graphite to L-glutamine is (5-10): (0.5-1).

8. The method for preparing a hot compress for pilots according to claim 7, characterized in that: In the step (2), the mass ratio of lauric acid to 3-aminopropanol, modified expanded graphite and curdlan is (45-90):(6-12):(5-10):(1-2).

9. The method for preparing a hot compress for pilots according to claim 8, characterized in that: In the step (3), the mass ratio of iron powder, vermiculite, activated carbon, temperature-controlling particles, sodium chloride and water is (900-950): (30-70): (40-60): (50-100): (20-40): (450-550).